An Intelligent Guardrail Context-Awareness System Based on Acceleration Sensors in Ubiquitous Sensor Networks - Seok-Woo Jang; Sung-Youn Cho; Gi-Sung Lee (International Journal of Distributed Sensor Networks)
A ubiquitous city (u-City) is a next-generation information-based city that combines state-of-the-art IT (information technology) infrastructures and ubiquitous information services. In general, the urban facilities of a u-City can be categorized into ground and underground facilities. This paper proposes a guardrail context-awareness system based on the analysis of acceleration sensors to manage guardrails systematically. Guardrails are one of the major ground facilities in a u-City. The suggested system generates alarms when acceleration sensors on guardrails recognize a certain level of physical shock. General information on the size and direction from the acceleration sensors is transmitted to the context-awareness system. The context-awareness system analyzes the scalar magnitude of the impacted shock, acceleration values to the x , y , and z directions, gravity direction of the sensors, and threshold values. It then determines if there is pronounced physical activity on the guardrail. Experimental results show that the suggested guardrail context-awareness approach accurately recognizes guardrail shock events that occur in various environments.